(untitled) (Global Journal of Medical Research, 2022)
The study briefly presents the public law-historical foundations of Hungarian medicine; describes the main peculiarities of the early, unchiseled regulation and the fact that the institutional care of the sick and poor was first dealt with by the clergy and the monastic orders. Real development began in the last third of the 19th century, and the first serious steps in public law were the changes at the legislative level of 1871 and 1876. By the 20th century, the pharmaceutical profession had developed, the organization of social security had been established, and after the Second World War the Ministry of Health was established in Hungary.